Meconium periorchitis is amenable to prompt radiological diagnosis - Rajendran Ramaswamy; Khairy Abdella; Samir Morsi Hegab (Wolters Kluwer Medknow Publications, 2023)
Scrotal swellings in neonates are very common. A 25-day-old male child had right-sided firm, nontender scrotal swelling. Ultrasound scan (USS) diagnosed as meconium periorchitis (MPO). At 70 days of age, repeat USS and plain abdominoscrotal radiograph confirmed MPO, and surgery was avoided. Radiological diagnosis and management of MPO are discussed.